2010
DOI: 10.1096/fj.10-161000
|View full text |Cite
|
Sign up to set email alerts
|

A role for inositol monophosphatase 1 (IMPA1) in salinity adaptation in the euryhaline eel (Anguilla anguilla)

Abstract: This study investigated the expression and tissue distribution of inositol monophosphatase (IMPA1) and characterized its role in salinity adaptation in the eel. The coding sequence of eel IMPA1 was determined and confirmed to be orthologous to the mammalian gene/enzyme by phylogenetic analysis and structural modeling. Quantitative real-time PCR and Western blot techniques indicated up to 17-fold increases in mRNA expression and 2-fold increases in protein abundance in major osmoregulatory tissues following tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 45 publications
4
36
1
Order By: Relevance
“…This is surprising given the fact that the synthesis of myo-inositol phosphate from G-6-P is the more rate-limiting step of the MIB pathway (Majumder et al, 1997), but does agree with a previous study that compared the regulation of the two enzymes (Sacchi et al, 2013). Significant upregulation or downregulation of IMPA1 mRNA under hyper-and hypo-osmotic challenge, respectively, has been reported in other teleost fishes (Evans and Somero, 2008;Kalujnaia et al, 2010;Whitehead et al, 2012). In leopard sharks, an osmoconforming species, inositol-related proteins have also been reported to be regulated in rectal gland and gill tissues in response to hypo-osmotic challenge (Dowd et al, 2010).…”
Section: Mib Enzymes In Tilapia Brain Robustly Respond To Plasma Osmosupporting
confidence: 87%
See 1 more Smart Citation
“…This is surprising given the fact that the synthesis of myo-inositol phosphate from G-6-P is the more rate-limiting step of the MIB pathway (Majumder et al, 1997), but does agree with a previous study that compared the regulation of the two enzymes (Sacchi et al, 2013). Significant upregulation or downregulation of IMPA1 mRNA under hyper-and hypo-osmotic challenge, respectively, has been reported in other teleost fishes (Evans and Somero, 2008;Kalujnaia et al, 2010;Whitehead et al, 2012). In leopard sharks, an osmoconforming species, inositol-related proteins have also been reported to be regulated in rectal gland and gill tissues in response to hypo-osmotic challenge (Dowd et al, 2010).…”
Section: Mib Enzymes In Tilapia Brain Robustly Respond To Plasma Osmosupporting
confidence: 87%
“…The MIB pathway utilizes two enzymes, myo-inositol phosphate synthase (MIPS) and inositol monophosphatase (IMPA), to generate myo-inositol endogenously from glucose-6-phosphate (G-6-P) in a two-step reaction (Geiger and Jin, 2006). The study by Fiol et al (Fiol et al, 2006b) was the first to identify upregulation of MIPS mRNA in response to acute hyperosmotic challenge in tilapia gill, and since then, several studies have confirmed induction of the MIB pathway in other euryhaline species exposed to salinity challenge (Evans and Somero, 2008;Kalujnaia et al, 2009;Kalujnaia et al, 2010;Kalujnaia et al, 2013). In mammals, IMPA has at least two isoforms, originating from different genes (Ohnishi et al, 2007;Shamir et al, 2001), while MIPS can have alternative splice variants (Seelan et al, 2009) derived from the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for salinity-dependent regulation of IMPA1 mRNA has recently been reported for other species of euryhaline fish, suggesting that the induction of the MIB pathway during hyperosmotic stress is an evolutionarily conserved trait of euryhaline teleosts. In European eel (Anguilla anguilla), IMPA1 mRNA increases in parallel to increased salinity (Kalujnaia and Cramb, 2009;Kalujnaia et al, 2010), and in killifish (Fundulus heteroclitus), IMPA1 mRNA is downregulated in response to a salinity decrease (Whitehead et al, 2012). The exquisite osmotic sensitivity of IMPA1 at both mRNA and protein levels makes this enzyme a robust indicator system for mechanistic studies of osmosensory signal transduction.…”
Section: Mips/impa Mrna Versus Protein Regulationmentioning
confidence: 99%
“…In addition, Kalujnaia and others (Kalujnaia and Cramb, 2009;Kalujnaia et al, 2010) have shown that the second enzyme of the MIB pathway (IMPA; EC 3.1.3.25) is also strongly induced at the mRNA level in the gill, kidney and intestine of European eels. These data on salinity effects at the transcript level suggest that the MIB pathway is physiologically important during osmotic stress because it generates high concentrations of the compatible organic osmolyte myo-inositol, which protects cells from salinity-induced damage (Yancey et al, 1982).…”
Section: Introductionmentioning
confidence: 98%
“…Induction of these two genes is also evident in other euryhaline fish exposed to acute salinity stress. For instance, elevated salinity increases MIPS abundance in O. niloticus and Anguilla anguilla (52) and IMPA1.1 abundance in Gillichthys mirabilis and A. anguilla (53)(54)(55)(56). The MIB pathway promotes the accumulation of high concentrations of the compatible osmolyte myo-inositol, which protects cells from salinity-induced damage (44,48,57).…”
Section: Discussionmentioning
confidence: 99%